Perovskite battery additive and application thereof
Patent Information
- Application Number
- CN202610876032.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-09-25
AI Technical Summary
但现有的改性添加剂仅能实现单一功能,无法同步兼顾结晶精准调控、多类型缺陷钝化、环境稳定性提升的多重改性需求,改性综合效果极具局限性
(1)本发明以氟化烷基铵硫氰酸盐作为钙钛矿电池添加剂,其能够精准调控钙钛矿的结晶过程,诱导晶面择优取向生长,促进大尺寸、高结晶度钙钛矿晶粒生长,显著减少薄膜内部深能级缺陷,提升电荷载流子的传输效率并降低非辐射复合损耗。
Smart Images

Figure CN122810012A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of perovskite battery technology, and in particular to a perovskite battery additive and its application. Background Technology
[0002] Organic-inorganic hybrid perovskite (ABX3 type, where A is an organic cation, B is a metal cation, and X is a halide anion) solar cells have experienced rapid technological iteration since their inception due to their numerous unique advantages, including ultra-high absorption coefficient, excellent carrier mobility, continuously tunable bandgap structure, and simple processing methods that allow for low-temperature solution fabrication. The ABX3 perovskite system effectively suppresses phase separation defects common in single-cation systems, significantly optimizes the quality of perovskite thin film formation and band structure, and comprehensively enhances the photovoltaic performance of the cells. It has become the mainstream research direction and core industrialization development path in the field of single-junction and tandem high-efficiency photovoltaic technology, possessing extremely high application value and market potential.
[0003] Although existing ABX3-type perovskite batteries have significantly improved the basic performance of batteries and can achieve ultra-high photoelectric conversion efficiency under laboratory conditions, several core technological bottlenecks remain unresolved in the large-scale commercialization of these batteries, severely limiting their industrialization. Firstly, the crystallization and nucleation processes in traditional solution processing are difficult to precisely control. Excessive crystallization rates and strong randomness in nucleation of perovskite easily lead to the formation of thin film microstructures characterized by fine grains, dense grain boundaries, and disordered crystal orientation. This results in a significant increase in the bulk defect density of the film, directly hindering efficient carrier transport and restricting battery performance improvement at the microstructural level. Furthermore, the non-ideal crystallization process further induces the generation of various deep-level defects, resulting in numerous unsaturated coordination sites, ion vacancies, and zero-valent metal defects within the perovskite film. These defects severely induce non-radiative recombination losses of carriers, causing a significant decrease in the battery's open-circuit voltage and fill factor. This prevents the device from achieving efficient and stable photoelectric conversion, becoming a core challenge restricting breakthroughs in battery photoelectric performance.
[0004] Currently, the industry mainly optimizes the performance of perovskite thin films through additive modification technology. However, existing modification additives can only achieve a single function and cannot simultaneously meet the multiple modification requirements of precise crystallization control, passivation of various types of defects, and improvement of environmental stability, resulting in a very limited overall modification effect. Furthermore, some traditional additives tend to remain inside the perovskite film after high-temperature annealing, hindering carrier transport channels, further reducing the photoelectric efficiency of the battery, and significantly decreasing the long-term reliability of the device. In addition, existing modification additives struggle to address the problems caused by moisture intrusion into the perovskite film during the perovskite film preparation process, which induces crystal phase transitions and material decomposition, leading to lead iodide residue, decreased crystal purity, and film aging failure. Summary of the Invention
[0005] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. Therefore, a first objective of the present invention is to provide a perovskite battery additive. A second objective of the present invention is to provide the application of this perovskite battery additive.
[0006] The inventive concept of this invention is as follows: This invention uses fluorinated alkylammonium thiocyanate as an additive for perovskite batteries, which can precisely control the crystallization process of perovskite, induce preferred orientation growth of crystal faces, promote the growth of large-size, highly crystalline perovskite grains, significantly reduce deep-level defects inside the thin film, improve the transport efficiency of charge carriers, and reduce non-radiative recombination losses.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a perovskite battery additive, the perovskite battery additive comprising fluorinated alkylammonium thiocyanate; the general chemical formula of the fluorinated alkylammonium thiocyanate is: C n H (2n+1-m) F m NH3SCN; where 1≤n≤99, 1≤m≤2n.
[0008] This invention uses fluorinated alkylammonium thiocyanate as an additive for perovskite solar cells. It can precisely control the crystallization process of perovskite, induce preferred orientation growth of crystal faces, promote the growth of large-size, highly crystalline perovskite grains, significantly reduce deep-level defects within the thin film, improve charge carrier transport efficiency, and reduce non-radiative recombination losses. This invention effectively solves the problems of insufficient stability and low photoelectric conversion efficiency in perovskite solar cells caused by the difficulty in precisely controlling crystallization kinetics.
[0009] Thiocyanate ions (SCN) in fluorinated alkylammonium thiocyanates - This can reduce the formation energy of the perovskite α phase, preferentially reducing the surface energy of the (100) crystal plane, and inducing the perovskite crystal to grow with a preferred orientation of the (100) crystal plane. This crystal plane has higher carrier mobility and lower trap state density, providing an efficient channel for carrier transport; SCN - It can trigger secondary recrystallization of perovskite, accelerate the Ostwald ripening process, achieve uniform grain size increase, reduce grain boundary density, and reduce carrier recombination losses caused by grain boundaries; SCN - It can form stable coordination with uncoordinated metal cations in perovskites, effectively passivating bulk defects such as metal vacancies (e.g., iodine vacancies); SCN - It can also significantly eliminate zero-valent metals (such as Pb) 0 The trap state (a strong carrier trap) further reduces carrier recombination sites.
[0010] The fluorine atom in fluorinated alkylammonium thiocyanate has strong electronegativity and can react with uncoordinated metal cations (such as Pb) in perovskite precursors. 2+ It forms strong coordination with ion vacancies (such as iodine vacancies), which significantly reduces the defect state density and nonradiative recombination loss; at the same time, it can also enhance the interface dipole moment, optimize the band arrangement, and improve the open-circuit voltage and charge extraction efficiency of the device.
[0011] The fluorinated alkylammonium thiocyanate of this invention possesses a synergistic effect of optimizing crystal quality and passivating defects, significantly extending the carrier lifetime of the formed perovskite film, increasing the quasi-Fermi level splitting value, reducing bulk and interfacial non-radiative losses, and effectively improving the device open-circuit voltage. Simultaneously, the preferred crystal orientation and low-defect surface of the fluorinated alkylammonium thiocyanate improve the interfacial contact between the perovskite and the electron and hole transport layers, reducing interfacial barriers and interfacial recombination, improving charge extraction and collection efficiency, and simultaneously increasing the device's short-circuit current density, fill factor, and photoelectric conversion efficiency. Furthermore, by optimizing the crystallization process, the fluorinated alkylammonium thiocyanate effectively reduces metal halide (such as PbI2) residue, inhibits perovskite surface degradation, improves the film's stoichiometry and structural integrity, and the fluorinated alkylammonium cations can accumulate at perovskite grain boundaries and the film surface, forming a quasi-2D passivation shell, achieving dual passivation of the bulk and interface, and significantly reducing non-radiative recombination losses.
[0012] Preferably, 1 ≤ n ≤ 50; more preferably, 1 ≤ n ≤ 20; and even more preferably, 1 ≤ n ≤ 10.
[0013] Preferably, 2≤m≤2n; more preferably, 3≤m≤2n. When the fluorinated alkyl thiocyanate has multiple fluorine substituents, i.e., when m≥2, the fluorinated alkyl thiocyanate has stronger electronegativity, can more efficiently coordinate unsaturated metal cation defects and reduce ion vacancy concentration, form a stronger interfacial dipole, and more effectively improve the open circuit voltage and fill factor.
[0014] Preferably, the fluorinated alkyl thiocyanate comprises at least one of 3-fluoro-2,2-dimethylprop-1-amine thiocyanate, 3,3-difluoro-2,2-dimethylprop-1-amine thiocyanate, 2-fluoro-2-methylbut-1-amine thiocyanate, 3,3,3-trifluoro-2,2-dimethylprop-1-amine thiocyanate, pentafluoroethyl-2-methylpropanethiocyanate, 2-fluoro-2-methylprop-1-amine thiocyanate, 3-fluoro-2-ethyl-2-methylprop-1-amine thiocyanate, 2-fluoroethylamine thiocyanate, 3,3,3-trifluoropropanethiocyanate, and 3-fluoropropanethiocyanate.
[0015] Preferably, the fluorinated alkyl thiocyanate has a branched structure. The branched structure of the fluorinated alkyl thiocyanate enhances the hydrophobicity of the formed perovskite light-absorbing layer, thereby improving the device's resistance to harsh external environments, delaying performance degradation during long-term use, and ultimately achieving a simultaneous improvement in the photoelectric conversion efficiency and long-term stability of the perovskite solar cell. Furthermore, the branched structure of the fluorinated alkyl thiocyanate also provides moderate steric hindrance, effectively decoupling the organic salt diffusion and perovskite crystallization process, suppressing excessively rapid crystallization and uncontrolled nucleation, successfully solving the problem of water vapor-induced crystallization disorder under normal pressure, and making it suitable for large-area uniform film formation.
[0016] Preferably, the fluorinated alkyl thiocyanate is prepared by a method comprising the following steps: dissolving thiocyanate and fluorinated alkylamine in an organic solvent, then heating under reflux, concentrating, cooling, and filtering to obtain the fluorinated alkyl thiocyanate.
[0017] Preferably, the molar ratio of thiocyanate to fluorinated alkylamine is (0.8~1.2):1; more preferably, the molar ratio of thiocyanate to fluorinated alkylamine is (0.9~1.1):1; and even more preferably, the molar ratio of thiocyanate to fluorinated alkylamine is (0.95~1.05):1.
[0018] Preferably, the thiocyanate includes at least one of ammonium thiocyanate, potassium thiocyanate, and sodium thiocyanate.
[0019] Preferably, the fluorinated alkylamine includes at least one selected from 3-fluoro-2,2-dimethylprop-1-amine, 3,3-difluoro-2,2-dimethylprop-1-amine, 2-fluoro-2-methylbut-1-amine, 3,3,3-trifluoro-2,2-dimethylprop-1-amine, 2-fluoro-2-methylprop-1-amine, 3-fluoro-2-ethyl-2-methylprop-1-amine, 2-fluoroethylamine, 3,3,3-trifluoropropylamine, and 3-fluoropropylamine.
[0020] Preferably, the fluorinated alkylamine comprises fluorinated alkylamine hydrochloride.
[0021] Preferably, the organic solvent includes at least one of methanol, ethanol, isopropanol, and acetonitrile.
[0022] Preferably, the heating reflux temperature is 60~120℃; more preferably, the heating reflux temperature is 70~90℃.
[0023] In a second aspect, the present invention provides a perovskite precursor solution, the perovskite precursor solution comprising a perovskite precursor, a solvent, and an additive; the additive comprising the fluorinated alkylammonium thiocyanate described in the first aspect.
[0024] Preferably, in the perovskite precursor solution, the molar ratio of fluorinated alkylammonium thiocyanate to perovskite precursor is 0.1% to 5%; more preferably, in the perovskite precursor solution, the molar ratio of fluorinated alkylammonium thiocyanate to perovskite precursor is 0.3% to 3%; even more preferably, in the perovskite precursor solution, the molar ratio of fluorinated alkylammonium thiocyanate to perovskite precursor is 0.5% to 1.5%.
[0025] Preferably, the perovskite precursor comprises an ABX3 structure, wherein A is an organic cation and / or an alkali metal cation, B is a metal cation, and X is a halide anion.
[0026] Preferably, the organic cation includes methylammonium cation (MA). + ) or formamidinium cation (FA + ).
[0027] Preferably, the alkali metal cation includes cesium ions (Cs). + ( ), at least one of rubidium ions, potassium ions, and sodium ions.
[0028] Preferably, the metal cation includes lead ions (Pb). 2+ ), tin ions (Sn) 2+ At least one of germanium ions and zinc ions. Preferably, the halide anion includes chloride ions (Cl... - ), bromide ions (Br) - ), iodide ions (I - At least one of the following.
[0029] Preferably, the concentration of the perovskite precursor in the perovskite precursor solution is 0.6M to 1.8M; more preferably, the concentration of the perovskite precursor in the perovskite precursor solution is 0.7M to 1.6M; and even more preferably, the concentration of the perovskite precursor in the perovskite precursor solution is 0.8M to 1.5M.
[0030] Preferably, the solvent includes at least one of dimethylformamide (DMF), dimethyl sulfoxide (DMSO), methylpyrrolidone (NMP), γ-butyrolactone, acetonitrile, methanol, and ethanol.
[0031] Preferably, the perovskite precursor solution further includes an organic cationic halide; more preferably, the organic cationic halide includes at least one of formamidinium iodide (FAI) and methylammonium chloride (MACl).
[0032] Thirdly, the present invention provides a perovskite light-absorbing layer, which is formed from the perovskite precursor solution described in the second aspect.
[0033] Fourthly, the present invention provides a perovskite solar cell, which, from bottom to top, includes a substrate, a hole transport layer, the perovskite light-absorbing layer described in the third aspect, an electron transport layer, and an electrode layer.
[0034] Preferably, a passivation layer is further provided between the perovskite light-absorbing layer and the electron transport layer.
[0035] Preferably, the substrate comprises fluorine-doped tin oxide (FTO) conductive glass or indium tin oxide (ITO) conductive glass.
[0036] Preferably, the material of the hole transport layer includes at least one of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid (MeO-2PACz), [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MeO-4PACz), MeOF-4PACz, (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid (Me-4PACz), 2-(3,6-dimethyl-9H-carbazole-9-yl)ethylphosphonic acid (Me-2PACz), poly(2-(9H-carbazole-9-yl)ethyl)phosphonic acid (Poly-2PACz), and poly[4-(9H-carbazole-9-yl)butyl]phosphonic acid (Poly-4PACz).
[0037] Preferably, the thickness of the perovskite light-absorbing layer is 300~800 nm; more preferably, the thickness of the perovskite light-absorbing layer is 400 nm~600 nm.
[0038] Preferably, the material of the passivation layer includes at least one of phenylethyl ammonium iodide (PEAI), piperazine monoiodide (PipI), propane-1,3-diammonium iodide (PDAI2), ethylenediamine diiodide (EDAI2), polymethyl methacrylate (PMMA), and cesium bromide (CsBr).
[0039] Preferably, the material of the electron transport layer includes titanium dioxide (TiO2), tin dioxide (SnO2), zinc oxide (ZnO), tungsten trioxide (WO3), niobium pentoxide (Nb2O5), and C. 60 One of [6,6]-phenyl-C61-butyrate methyl ester (PCBM), naphthalimide (NDI), and their derivatives; more preferably, the material of the electron transport layer includes SnO2 and C 60 .
[0040] Preferably, the thickness of the electron transport layer is 40-80 nm; more preferably, the thickness of the electron transport layer is 50-70 nm.
[0041] Preferably, the material of the electrode layer includes at least one of silver, gold, copper, and bismuth.
[0042] Preferably, the thickness of the electrode layer is 100~150nm; more preferably, the thickness of the electrode layer is 110~130nm.
[0043] Fifthly, the present invention provides a method for preparing a perovskite solar cell, comprising the following steps: S1: Prepare a hole transport layer on the substrate; S2: Coating the perovskite precursor solution described in the second aspect onto the hole transport layer, and then annealing to obtain a perovskite light-absorbing layer. S3: An electron transport layer is prepared on the perovskite light-absorbing layer; S4: An electrode layer is prepared on the electron transport layer to obtain the perovskite solar cell.
[0044] Preferably, a passivation layer is first prepared on the perovskite light-absorbing layer, and then an electron transport layer is prepared on the passivation layer.
[0045] The beneficial effects of this invention are: (1) In this invention, fluorinated alkylammonium thiocyanate is used as an additive for perovskite batteries. It can precisely control the crystallization process of perovskite, induce preferred orientation growth of crystal faces, promote the growth of large-size, highly crystalline perovskite grains, significantly reduce deep-level defects inside the film, improve the transport efficiency of charge carriers and reduce non-radiative recombination loss.
[0046] (2) The fluorinated alkylammonium thiocyanate of the present invention has the synergistic effect of optimizing crystal quality and passivating defects, which can significantly prolong the carrier lifetime of the formed perovskite film, increase the quasi-Fermi level splitting value, reduce bulk and interfacial non-radiative losses, and effectively improve the open-circuit voltage of perovskite solar cell devices. At the same time, the preferred crystal orientation and low-defect surface of the fluorinated alkylammonium thiocyanate can improve the interfacial contact between perovskite and electron transport layer and hole transport layer, reduce interfacial barriers and interfacial recombination, improve charge extraction and collection efficiency, and simultaneously improve the short-circuit current density, fill factor and photoelectric conversion efficiency of perovskite devices.
[0047] (3) Compared with alkylammonium thiocyanate, the fluorine atom in the fluorinated alkylammonium thiocyanate of the present invention has strong electronegativity, which can form strong coordination with uncoordinated metal cations and ion vacancies in perovskite precursors, significantly reducing defect state density and nonradiative recombination loss; at the same time, it can also enhance the interface dipole moment, optimize the band arrangement, and improve the open circuit voltage and charge extraction efficiency of the device.
[0048] (4) The branched structure of the fluorinated alkyl thiocyanate of the present invention can enhance the hydrophobicity of the formed perovskite light-absorbing layer, thereby improving the device's resistance to harsh external environments, delaying the performance degradation problem during long-term use, and ultimately achieving a simultaneous improvement in the photoelectric conversion efficiency and long-term stability of perovskite solar cells. In addition, the branched structure of the fluorinated alkyl thiocyanate also provides moderate steric hindrance, which can effectively decouple the diffusion of organic salts from the perovskite crystallization process, suppress the problem of excessively fast crystallization rate and uncontrolled nucleation, and successfully solve the problem of water vapor-induced crystallization disorder under normal pressure, making it suitable for large-area uniform film formation.
[0049] (5) The addition of the fluorinated alkyl thiocyanate of the present invention to the perovskite precursor solution and the subsequent preparation of a perovskite solar cell can significantly improve the performance of the perovskite solar cell. The prepared perovskite solar cell has a photoelectric conversion efficiency of up to 23.46% and a short-circuit current density of up to 25.56 mA / cm². 2 . Attached Figure Description
[0050] Figure 1 The graphs show the stability test results of the perovskite solar cell devices in Example 5 and Comparative Example 1. Detailed Implementation
[0051] To enable those skilled in the art to better understand this application, the present invention will be further described in detail below with reference to embodiments. However, it should be understood that the following embodiments are merely preferred embodiments of the present invention, and the scope of protection of the present invention should be determined by the scope defined in the claims.
[0052] In the description of this invention, it should be noted that unless specific conditions are specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available products. Furthermore, to better illustrate this invention, numerous specific details are provided in the following detailed embodiments. Those skilled in the art should understand that this invention can be practiced even without certain specific details. In some embodiments, raw materials, methods, and means well known to those skilled in the art are not described in detail in order to highlight the main points of this invention.
[0053] Unless otherwise expressly stated, throughout the specification and claims, the term "comprising" or its variations such as "including" or "comprising" shall be understood to include the stated elements or components without excluding other elements or other components.
[0054] In the perovskite solar cell of the present invention, the thickness of the hole transport layer and the passivation layer can be less than 10 nm, and the present invention does not impose any special limitation.
[0055] Example 1 This embodiment provides a Cs 0.05 FA 0.95 The PbI3 perovskite precursor solution was prepared using the following method: Step 1: Weigh 1643 mg formamidinium iodide (FAI), 4610 mg lead iodide (PbI2), 130 mg cesium iodide (CsI), and 101 mg methylammonium chloride (MACl), and dissolve them in 10 mL of a mixed solvent (DMF to NMP volume ratio of 8:1). Stir at room temperature for 10 hours, filter through a disposable polytetrafluoroethylene filter membrane to obtain the filtrate. The filtrate contains Cs... 0.05 FA 0.95 The concentration of PbI3 is 1M; Step 2: Dissolve ammonium thiocyanate and 3,3-difluoro-2,2-dimethylpropyl-1-amine hydrochloride in methanol at a molar ratio of 1.05:1, heat to 65~68℃ under normal pressure and reflux, then concentrate, cool and filter to obtain 3,3-difluoro-2,2-dimethylpropyl-1-amine thiocyanate; Step 3: Add 3,3-difluoro-2,2-dimethylpropyl-1-aminethiocyanate from Step 2 to the filtrate from Step 1. 3,3-difluoro-2,2-dimethylpropyl-1-aminethiocyanate and Cs 0.05 FA 0.95 The molar ratio of PbI3 perovskite precursor was 1% (i.e., 0.0001 mol), yielding Cs. 0.05 FA 0.95 PbI3 perovskite precursor solution.
[0056] Example 2 This embodiment provides a Cs 0.05 FA 0.95 The PbI3 perovskite precursor solution differs from Example 1 in that 3,3-difluoro-2,2-dimethylpropyl-1-aminethiocyanate and Cs 0.05 FA 0.95 The molar ratio of PbI3 perovskite precursor was 0.5% (i.e., 0.00005 mol), and all other parameters were the same as in Example 1.
[0057] Example 3 This embodiment provides a Cs 0.05 FA 0.95 The PbI3 perovskite precursor solution differs from Example 1 in that 3,3-difluoro-2,2-dimethylpropyl-1-aminethiocyanate and Cs 0.05 FA 0.95 The molar ratio of PbI3 perovskite precursor was 1.5% (i.e., 0.00015 mol), and the rest was the same as in Example 1.
[0058] Example 4 This embodiment provides a Cs 0.05 FA 0.95 The PbI3 perovskite precursor solution was prepared using the following method: Step 1: Same as Step 1 in Example 1; Step 2: Dissolve ammonium thiocyanate and 3-fluoro-2,2-dimethylprop-1-amine hydrochloride in methanol at a molar ratio of 1.05:1, heat to 65~68℃ under normal pressure and reflux, then concentrate, cool and filter to obtain 3-fluoro-2,2-dimethylprop-1-amine thiocyanate. Step 3: Add 3-fluoro-2,2-dimethylprop-1-aminethiocyanate from Step 2 to the filtrate from Step 1. 3-fluoro-2,2-dimethylprop-1-aminethiocyanate and Cs 0.05 FA 0.95 The molar ratio of PbI3 perovskite precursor was 1% (i.e., 0.0001 mol), yielding Cs. 0.05 FA 0.95 PbI3 perovskite precursor solution.
[0059] Example 5 This embodiment provides a perovskite solar cell, which, from bottom to top, includes a substrate, a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, and an electrode layer. It is fabricated using the following method: Step 1: Clean the ITO conductive glass with glass cleaner, deionized water, acetone and isopropanol in sequence for 20 minutes. After ultrasonic cleaning, purge with nitrogen and clean with ultraviolet ozone cleaner for 20 minutes. Step 2: Slit-coat the conductive surface of ITO conductive glass with a methanol solution of 0.5 mg / mL Me-4PACz and anneal at 100°C for 5 min to obtain the hole transport layer. Step 3: Take Cs from Example 1 0.05 FA 0.95 PbI3 perovskite precursor solution was slit-coated onto the hole transport layer, and then annealed at 150 °C for 15 min to form a Cs layer with a thickness of 500 nm. 0.05 FA 0.95 PbI3 perovskite light-absorbing layer; Step 4: Slit-coat a 1 mg / mL PipI isopropanol solution onto the perovskite light-absorbing layer to form a passivation layer; Step 5: Vacuum evaporation of C onto the passivation layer 60 After atomic deposition of SnO2, an electron transport layer with a total thickness of 60 nm is formed; Step 6: Deposit Ag on the electron transport layer to form an Ag electrode with a thickness of 120 nm.
[0060] Example 6 This embodiment provides a perovskite solar cell, which differs from Embodiment 5 in that the perovskite precursor solution used in step 3 is the Cs solution from Embodiment 2. 0.05 FA 0.95 The PbI3 perovskite precursor solution was used, and the rest of the process was the same as in Example 5.
[0061] Example 7 This embodiment provides a perovskite solar cell, which differs from Embodiment 5 in that the perovskite precursor solution used in step 3 is the Cs solution from Embodiment 3. 0.05 FA 0.95 The PbI3 perovskite precursor solution was used, and the rest of the process was the same as in Example 5.
[0062] Example 8 This embodiment provides a perovskite solar cell, which differs from Embodiment 5 in that the perovskite precursor solution used in step 3 is the Cs solution from Embodiment 4. 0.05 FA 0.95 The PbI3 perovskite precursor solution was used, and the rest of the process was the same as in Example 5.
[0063] Comparative Example 1 This comparative example provides a perovskite solar cell, which differs from Example 5 in that the perovskite precursor solution used in step 3 is the filtrate prepared in step 1 of Example 1, without any additives. All other aspects are the same as in Example 5.
[0064] Comparative Example 2 This comparative example provides a perovskite solar cell, which differs from Example 5 in that the additive in the perovskite precursor solution used in step 3 is tetrabutylammonium thiocyanate, while the rest is the same as in Example 5.
[0065] Performance testing The performance of the perovskite solar cells in Examples 5-8 and Comparative Examples 1-2 was tested respectively, and the test results are shown in Table 1.
[0066] Table 1. Performance of perovskite solar cells in Examples 5-8 and Comparative Examples 1-2
[0067] As shown in Table 1, compared with Comparative Example 1, the perovskite solar cells prepared with the perovskite precursor solution containing fluorinated alkylammonium thiocyanate (Examples 5-8) can significantly improve the power conversion efficiency (PCE) and short-circuit current density (J / L) of the perovskite solar cells. SC ), open circuit voltage (V) OCThe perovskite crystallization process can be precisely controlled by fluorinated alkylammonium thiocyanate, which induces preferred orientation growth of crystal faces, promotes the growth of large-size, highly crystalline perovskite grains, significantly reduces deep-level defects inside the thin film, improves the charge carrier transport efficiency and reduces non-radiative recombination loss, thereby improving the photoelectric performance of perovskite solar cells.
[0068] Compared to Comparative Example 2, the perovskite solar cells of Examples 5-8 exhibit superior photoelectric performance (higher fill factor, open-circuit voltage, and photoelectric conversion efficiency). This is because, compared to alkylammonium thiocyanate, the fluorine atom in fluorinated alkylammonium thiocyanate has strong electronegativity and a stronger coordination ability, allowing it to interact with uncoordinated Pb atoms in the perovskite precursor. 2+ The iodine vacancies form a stronger coordination effect (stronger than alkylammonium thiocyanate), resulting in a more significant bulk passivation effect. In addition, fluorine atoms in fluorinated alkylammonium thiocyanate can enhance the interfacial dipole moment and optimize the band arrangement, which will also improve the open-circuit voltage and charge extraction efficiency of the device to some extent.
[0069] Comparing Examples 5-7, it is evident that the amount of fluorinated alkylammonium thiocyanate added to the perovskite precursor solution affects battery performance. A low amount of fluorinated alkylammonium thiocyanate leads to insufficient passivation, while a high amount easily forms an insulating enrichment layer, hindering carrier transport. When the amount of fluorinated alkylammonium thiocyanate in the perovskite precursor solution reacts with Cs... 0.05 FA 0.95 When the molar ratio of PbI3 perovskite precursor is 1%, fluorinated alkylammonium thiocyanate can effectively passivate defects without impairing the film transport properties.
[0070] Compared to Example 8, the perovskite solar energy of Example 5 is superior. This is because the additive in the perovskite precursor solution of Example 5 is 3,3-difluoro-2,2-dimethylpropyl-1-aminethiocyanate, which contains difluoro substituents and has stronger electronegativity, enabling more efficient coordination of unsaturated Pb. 2+ The defects reduce the iodine vacancy concentration and form a stronger interfacial dipole, thereby more effectively improving the photoelectric conversion efficiency, short-circuit current density, and fill factor. In addition, the difluorinated structure of 3,3-difluoro-2,2-dimethylpropyl-1-aminethiocyanate is superior to the monofluorinated structure in terms of defect passivation, bandgap modulation, and hydrophobicity, thus achieving optimal photoelectric conversion efficiency.
[0071] The stability of the perovskite solar cell devices of Example 5 and Comparative Example 1 was tested. The test method was as follows: under a nitrogen atmosphere, at 25°C, and with continuous illumination at a light intensity of 1000 W / m² for 6 weeks, the optimal PCE degradation was recorded. The test results are as follows: Figure 1 As shown.
[0072] from Figure 1 As can be seen, Example 5 and Comparative Example 1 showed similar degradation trends in the first week. However, after one week, the degradation rate of Example 5 was significantly lower than that of Comparative Example 1. After six weeks, the device in Example 5 still maintained more than 80% of its initial PCE, while the Comparative Example 1, which did not use additives in the perovskite precursor solution, only had 60% of its initial PCE. This is because the branched structure of the additives in the perovskite precursor solution in Example 5 can enhance the hydrophobicity of the perovskite light-absorbing layer, thereby improving the device's resistance to harsh external environments, delaying performance degradation during long-term use, and ultimately improving the long-term stability of perovskite solar cells.
[0073] In summary, the present invention incorporates fluorinated alkylammonium thiocyanate into the perovskite precursor solution, which synergistically optimizes crystal quality and passivates defects. This significantly extends the carrier lifetime of the formed perovskite film, increases the quasi-Fermi level splitting value, reduces bulk and interfacial non-radiative losses, and effectively improves the open-circuit voltage of perovskite solar cell devices. Simultaneously, the preferred crystal orientation and low-defect surface of fluorinated alkylammonium thiocyanate improve the interfacial contact between the perovskite and the electron and hole transport layers, reduces interfacial barriers and recombination, and enhances charge extraction and collection efficiency, thereby simultaneously increasing the short-circuit current density, fill factor, and photoelectric conversion efficiency of the perovskite device.
[0074] This invention uses fluorinated alkylammonium thiocyanate as an additive for perovskite solar cells, achieving a synergistic effect of multiple functions including crystallization control, defect passivation, interface optimization, and stability enhancement. It overcomes the technical bottlenecks of existing technologies, such as single-function additives, difficulty in balancing photovoltaic performance and stability, residual pollution, and poor compatibility with atmospheric pressure fabrication. Based on this additive, the perovskite solar cell fabrication method provided by this invention is simple, efficient, and widely applicable, suitable for large-area industrial production. The resulting perovskite solar cells are highly efficient and stable, possessing significant industrial application value.
[0075] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A perovskite battery additive, characterized in that, The perovskite battery additive includes fluorinated alkylammonium thiocyanate; the general chemical formula of the fluorinated alkylammonium thiocyanate is: C n H (2n+1-m) F m NH3SCN; where 1≤n≤99, 1≤m≤2n.
2. The perovskite battery additive according to claim 1, characterized in that, The fluorinated alkyl thiocyanates include at least one of 3-fluoro-2,2-dimethylprop-1-amine thiocyanate, 3,3-difluoro-2,2-dimethylprop-1-amine thiocyanate, 2-fluoro-2-methylbut-1-amine thiocyanate, 3,3,3-trifluoro-2,2-dimethylprop-1-amine thiocyanate, pentafluoroethyl-2-methylpropanethiocyanate, 2-fluoro-2-methylprop-1-amine thiocyanate, 3-fluoro-2-ethyl-2-methylprop-1-amine thiocyanate, 2-fluoroethylamine thiocyanate, 3,3,3-trifluoropropanethiocyanate, and 3-fluoropropanethiocyanate.
3. The perovskite battery additive according to claim 1, characterized in that, The fluorinated alkyl thiocyanate has a branched structure.
4. A perovskite precursor solution, characterized in that, The perovskite precursor solution comprises a perovskite precursor, a solvent, and the perovskite battery additive according to any one of claims 1 to 3.
5. The perovskite precursor solution according to claim 4, characterized in that, The perovskite precursor includes an ABX3 structure, wherein A is an organic cation and / or an alkali metal cation, B is a metal cation, and X is a halide anion; And / or, the solvent includes at least one of dimethylformamide, dimethyl sulfoxide, methylpyrrolidone, γ-butyrolactone, acetonitrile, methanol, and ethanol.
6. The perovskite precursor solution according to claim 4, characterized in that, The molar ratio of the fluorinated alkylammonium thiocyanate to the perovskite precursor is 0.1% to 5%; And / or, the concentration of the perovskite precursor is 0.6M to 1.8M.
7. The perovskite precursor solution according to claim 4, characterized in that, The perovskite precursor solution also includes organic cationic halides.
8. A perovskite light-absorbing layer, characterized in that, It is formed from the perovskite precursor solution according to any one of claims 4 to 7.
9. A perovskite battery, characterized in that, The perovskite solar cell, from bottom to top, includes a substrate, a hole transport layer, the perovskite light-absorbing layer as described in claim 8, an electron transport layer, and an electrode layer.
10. A method for preparing a perovskite solar cell, characterized in that, Includes the following steps: S1: Prepare a hole transport layer on the substrate; S2: Coat the perovskite precursor solution according to any one of claims 4 to 7 onto the hole transport layer, and obtain a perovskite light-absorbing layer after annealing. S3: An electron transport layer is prepared on the perovskite light-absorbing layer; S4: An electrode layer is prepared on the electron transport layer to obtain the perovskite solar cell.